Passive adaptive façades : examples from COST TU1403 working group 1 - Mazzucchelli, Enrico Sergio (2019)
ABSTRACT: Buildings often adopt strategies based on the integration of solutions and technologies in façades capable of changing their behaviour in time to improve energy efficiency and comfort. Considering that the envelope is the main parameter that influences the energy performance of buildings, façade elements with adaptive features can provide the buildings the necessary flexibility needed in terms of energy flow and thermal comfort in the context of nZEB, where the buildings must be interactive in the zero energy and smart city context. Several different types of adaptive façade concepts have already been developed, and an increase in emerging, innovative solutions is expected in the near future. However, when referring to adaptive technologies, two main categories can be distinguished. Adaptive technologies, which rely on passive design to improve building energy efficiency and comfort, and active technologies which include renewable harvesting. The aim of this paper is to provide several examples of passive adaptive technologies and their performance features from COST TU1403 Working Group 1 database.